PENGGUNAAN MODEL PEMBELAJARAN PICTURE AND PICTURE MENINGKATKAN HASIL BELAJAR SENI RUPA DI SEKOLAH MENENGAH PERTAMA - Yulia Rahma Sari; Ramalis Hakim (Universitas Negeri Padang, 2020)
In the teaching and learning process the teacher plays an important role in guiding students to be active. Because teachers who are active and creative can create a conducive situation in providing subject matter. But for that we need an appropriate learning model when the authors make preliminary observations, the writer observes that the teacher still uses less appropriate learning models so that the classroom atmosphere is boring because the teacher uses the media jus a blackboard, delivery by lecture, lack of feedback between teachers and students. This causes a reduction in student interest in learning which has an impact on the low learning outcomes of students in learning fine arts. Based on the google scholar search, the authors found many studies that examined the use of the picrture and picture learning model, therefore the authors examined the use of the picture and picture learning model. The purpose of writing scientific articles is to determine the accuracy of using the picture and picture learning model as a result of learning fine arts. The method that I use in this research is literature study. The data that the authors get comes from the aritkel related to the variables. The writer got this artiekel from Google Schlar, which numbered 12 reference articles, that the average learning outcome after using the picture and picture learning model was 78.97. From these conclusions it proves that after using the picture and pictrure model it can increase studentKeywords: Picture And Picture Learning Model, Learning Outcomes, FineArt